Economic Policy Uncertainty and the Volatility of Sovereign CDS Spreads - Burkhard Raunig (Oesterreichische Nationalbank (OeNB), 2018)
Multipliers estimated for sixteen major economies predict that 1% more economic policy uncertainty (EPU) produces about 0.3% - 0.8% more sovereign CDS volatility. The impact of EPU is strong but short-lived. US EPU is an important additional source of CDS volatility for European countries, Japan, China, and South Korea. European EPU does, in contrast, not affect the CDS volatility of other countries.
Keywords: D80; E66; G18; 330; Credit default swap; Economic policy uncertainty; Sovereign credit risk; Volatility